2009
DOI: 10.1007/s10517-009-0471-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of Serotoninergic System in the Development of Gastrointestinal Diseases

Abstract: Experimental gastroduodenal ulcer was simulated after pre-injection of serotonin; gastroesophageal reflux disease and duodenogastral reflux were induced. Activation of the serotoninergic system promoted the development of alteration processes in gastroduodenal ulcer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…First, consistent with prior research, we found a subset of patients with both depressive and gastrointestinal disorders [28][29][30][31]. The autonomic nervous system and serotonergic systems are implicated in gastrointestinal functions: gastric smooth muscle cells express 5-HT1 and 5-HT2 receptors where serotonin induces contractions in the gastric fundus and activity at 5-HT3 receptors caused gastric relaxation and accelerated intestinal transit [32,33]. The common gastrointestinal side effects associated with SSRI antidepressants are illustrative of this relationship, however, so too are reports that ondansetron, a 5-HT3 receptor antagonist, improves depressive symptoms [32,34].…”
Section: Discussionsupporting
confidence: 88%
“…First, consistent with prior research, we found a subset of patients with both depressive and gastrointestinal disorders [28][29][30][31]. The autonomic nervous system and serotonergic systems are implicated in gastrointestinal functions: gastric smooth muscle cells express 5-HT1 and 5-HT2 receptors where serotonin induces contractions in the gastric fundus and activity at 5-HT3 receptors caused gastric relaxation and accelerated intestinal transit [32,33]. The common gastrointestinal side effects associated with SSRI antidepressants are illustrative of this relationship, however, so too are reports that ondansetron, a 5-HT3 receptor antagonist, improves depressive symptoms [32,34].…”
Section: Discussionsupporting
confidence: 88%
“…Through these receptors, 5-HT regulates the contractile activity of smooth muscles. Serotonin induces contractions of the smooth-muscle cells of the fundal compartment of the stomach during reaction with 5-HT 2B receptors [18]. During ulcer relapse, we noted significantly raised levels of NA, DA and free 5-HT.…”
Section: Discussionmentioning
confidence: 76%
“…First, consistent with prior research, we found strong associations between depressive and gastrointestinal disorders (Fond et al, 2014; Foster & Neufeld, 2013; Neuendorf, Harding, Stello, Hanes, & Wahbeh, 2016; Taylor & Holscher, 2020). The autonomic nervous system and serotonergic systems are implicated in gastrointestinal functions: gastric smooth muscle cells express 5-HT1 and 5-HT2 receptors where serotonin induces contractions in the gastric fundus and activity at 5-HT3 receptors caused gastric relaxation and accelerated intestinal transit (Kindt & Tack, 2007; Lychkova, 2009). The common gastrointestinal side effects associated with SSRI antidepressants are illustrative of this relationship, however, so too are reports that ondansetron, a 5-HT3 receptor antagonist, improves depressive symptoms (Bétry et al, 2011; Kindt & Tack, 2007).…”
Section: Discussionmentioning
confidence: 99%